POPULATION DYNAMIC OF PARASITE DIVERSITY OF THE PERUVIAN ROCK SEABASS, PARALABRAX HUMERALIS (TELEOSTEI: SERRANIDAE) ON CHORRILLOS, LIMA, PERU - Iannacone, José (2009)
A research on some community components of parasitefauna of 369 Paralabrax humeralis Valenciennes, 1828 collected from Chorrillos Fishmarket, Lima, Peru, between October 1996 and February 2009 and necropsied to study population dynamic of parasite diversity was conducted. Of the fishes collected, 205 were males and 164 females. Fishes showed a total length (TL) between 18.00 and 44.60 cm (mean = 22.86± 4.27). Metazoan parasites were collected and counted employing conventional techniques. 5731 specimens in total during all the survey, with a mean abundance of 15.53 (0-207) were collected and not correlated to TL of Peruvian Rock Seabass. The mean parasite species richness was 2.34 (1-5) and also not correlated to host´s TL. 26 hosts were not parasited (7.1%). 70 hosts (19 %) showed infection with 1 parasite species, and 94 (25.5 %), 118 (32%), 52 (14.1%) and finally nine (2.4 %) had multiple infection, 2, 3, 4 and 5 parasite species, respectively. Ten species of metazoan parasites were collected: monogenean Hemitagia galapagensis (Meserve, 1938) Sproston 1946, trematod Helicometra fasciata (Rudolphi, 1819), cestods Diphyllobothrium pacificum (Nybelin, 1931) and one Trypanorhyncha gen. sp. not identificated, acanthocephalan Corynosoma obtuscens Lincicome 1943; nematodes Dycheline (Cucullanellus) sp. and Philometra sp. and copepods Acantholochus paralabracis Luque & Bruno, 1990; Caligus quadratus (Shiino, 1954), and Hatschekia amphiprocessa Castro & Baeza, 1986. Patterns on structure and composition of parasite assemblage of P. humeralis were observed: 1) dominance of an ectoparasitic monogenea; 2) correlation between body total length of the host and parasite abundance; 3) No parasite species showed influence of host sex on parasite abundance and prevalence; 4) isolationist and not interactive community (index of interactivity [CC ] for endoparasites and interactive community for ectoparasites, 5) all parasites 50 showed an aggregated distribution, and 6) for seven parasites and for total parasites an inter-year variation and seasonallity in relation to prevalence and abundance of infection.